Thyroid cervico-thoracic teratoma in a 14-month old child - Mohammad Mohammad (Wolters Kluwer Medknow Publications, 2010)
Cervical teratoma (CT) is a rare disease which accounts for approximately three to five per cent of all teratomas in children. Airway compromise is the most serious postnatal complication of cervical teratoma. Prenatal diagnosis is crucial for early recognition of neck masses that could obstruct the airway. We present our experience in the management of a huge cervico-thoracic teratoma in a 14-month old Nigerian child.